Wartość odżywcza mięsa zachowawczych stad kacze - Wołoszyn, Janina; Książkiewicz, Juliusz; Biernat, Jadwiga; Okruszek, Andrzej (Nutritional Value of Duck Meat from Conservative Flocks, 2008)
The chemical composition of muscles of two conservative flocks of duck (P33, K2) was investigated. There were no differences in the moisture and protein contents in the investigated muscles. Although the differences in the lipids and cholesterol content were stated, they are not significant from the practical point of view. The higher content of lipids was observed in leg (1.40-1.73%) than in breast (0.8-1.16%) muscles for two flocks. The muscles of the investigated ducks comprised of all essential amino acids. The amino acid proportion of meat proteins depended on the kind of flocks. The ILE and VAL were amino acids which limited the biological value of meat protein. The protein of P33 breast muscles was characterized by the higher content of PRO and ASX than K2 one. The protein of breast and leg muscles of K2 comprised of more PHE and HIS in comparison with P33. The LYS was characterized by the highest value of limited amino acids index (R=157.8-164.4) and thereby possessed the highest biological value. The fatty acids from C4 to C22:6 in muscles of investigated birds were identified. The highest content of C18:1 and C16 was stated. The kind of flock was affected the following fatty acids: C8, C10, C12, C14,, C18:3, C20:4,C22:6. The unsaturated fatty acids (UFA) were predominant for all muscles (50.12-60.62% ). The polyunsaturated fatty acids (PUFA) amounted to 25.97-30.44% and the higher level of PUFA was established in K2 muscles. The UFA/SFA ratio was 1.19-1.86, the PUFA/SFA ratio was 0.63-0.92 and the PUFA n-6/n-3 ratio was 5.09-5.85. The lipids from K2 leg muscles were characterized by the best fatty acid profile among the investigated muscles. It is hard to say which investigated strain is more profitable because some components were more favorable in the P33 and others in K2 muscles. Taking into consideration the lipids and cholesterol content, the P33 breast muscles were the most suitable, but K2 leg muscles were characterized by the highest biological value of proteins and by the best profile of fatty acids. It is evident that muscles from flocks examined have been characterized by high nutritional value. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 51-61